2011
DOI: 10.15283/ijsc.2011.4.2.105
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Proliferation and Behavior of Retinal Pigment Epithelial Cells on Purified Alginate Films

Abstract: Background and Objectives: Alginate, an anionic polysaccharide distributed widely in the cell walls of brown algae, is used in biomedical applications. However, alginate's performance as a biomaterial, has limited by its several contamination such as endotoxins, proteins and polyphenols. Methods and Results: To overcome this problem, we have developed using modified Korbutt method for alginate purification. After purification, we made alginate films and used for retinal pigment epithelial cell (RPEs) regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Before testing for cell viability, each sample was observed to determine cell migration within the porous structure of the scaffold; then each sample of 100 µl was pipetted into a 96‐well plate and the absorbance at 570 nm, using an ELISA microplate reader (E‐Max, Molecular Devices, Sunnyvale, CA, USA), was yielded as a function of viable cell number. The rate of tetrazolium (MTT) reduction is proportional to the rate of cell viability (Jeong et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Before testing for cell viability, each sample was observed to determine cell migration within the porous structure of the scaffold; then each sample of 100 µl was pipetted into a 96‐well plate and the absorbance at 570 nm, using an ELISA microplate reader (E‐Max, Molecular Devices, Sunnyvale, CA, USA), was yielded as a function of viable cell number. The rate of tetrazolium (MTT) reduction is proportional to the rate of cell viability (Jeong et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The decellularized SIS was washed with saline solution, followed by 0.1% peracetic acid, and sliced at about 7 cm in the longitudinal direction. The slices were freeze‐dried using a freeze dryer (model FDU‐540, EYELA, Japan) at –80°C for 48 h, and the dried SIS was obtained using a cryogenic laboratory mill (SPEX 6750 Freezer Mill, SPEX, NJ, USA) at –198°C to yield a SIS powder of particle size < 180 µm (Kim et al ., ; Oh et al ., ; Yoshioka et al ., ; Giordano et al ., ; Jeong et al ., ; Jang et al ., ; Song et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…AMD) or by surgical excision of CNV may maintain photoreceptor function in patients (Itaya et al ., ). There exist methods of transplantation of RPE cells; one is RPE suspensions (Radtke et al ., ; Aramant et al ., ; Woch et al ., ), which form a monolayer when transplanted into the subretinal space; another is cultivating RPE cells on a scaffold (Jeong et al ., ). However, using the former method to transplant RPE cells is often accompanied by significant cell loss, migration and fibrosis at the subretinal space after transplantation (Lopez et al ., ; Kubota et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Hunt et al further demonstrated the potential of RGD-alginate scaffolds for the derivation, transport, and transplantation of neural retina and RPE [44]. Purified alginate films have also been manufactured and used as a scaffold of for RPE cells [74]. This study indicated that purified alginate films allowed higher cell proliferative rate and phenotypic expression compared with nonpurified alginate films.…”
Section: Scaffold Biocompatibilitymentioning
confidence: 96%